Exploring the Effect of Scripted Roles on Cognitive Presence in Asynchronous Online Discussions - Larisa Olesova; Margaret Slavin; Jieun Lim (Online Learning, 2016)
The purpose of this study was to identify the effect of scripted roles on students’ level of cognitive presence in asynchronous online threaded discussions. A mixed methods design was used to investigate: (1) what level of cognitive presence is achieved by students’ assigned roles in asynchronous online discussions; (2) differences between students’ cognitive presence when the asynchronous online discussions occur during a 5-week intensive summer courses versus 15-week regular semesters (fall and spring); and (3) the impact of the types of questions on students’ cognitive presence in role-based asynchronous online discussions across three semesters in an online introductory nutrition course. The participants of this study were 129 undergraduate students at a major public University in the mid-Atlantic region of the United States. The results of this research corresponds to the findings of previous research that scripted roles can be an effective strategy to improve both learning processes and outcomes. In addition, this study didn’t find any differences in students’ level of cognitive presence when they enrolled in 5-week summer courses or 15-week regular semesters in fall and spring. Finally, this study found evidence that the types of questions related to the level of cognitive presence, i.e., higher level questions can lead to higher level of cognitive presence and vice versa.